Literasi Informasi Digital: Tantangan Bagi Para Santri Dalam Menjalankan Peran Sebagai Global Citizen (Studi Kasus Pada Pondok Pesantren Darussa”Adah Bandar Lampung) - ., Karomani; Nurhaida, Ida; Aryanti, Nina Yudha; Windah, Andi; Purnamayanti, Arnila (Universitas Islam Negeri Raden Intan Lampung, 2021)
The purpose of this research is to increase knowledge and understanding as well as digital literacy of the Darussa'adah Islamic Boarding School students in Bandar Lampung about the importance of access and adoption of healthy and safe internet technology. The research method used is descriptive quantitative with data collection techniques using surveys. The results of this study indicate that the mastery of the concept of global citizenship by the students still cannot be understood explicitly, so that further understanding of the students is needed. Most of the students of Darussa'adah Islamic Boarding School still do not have digital literacy skills effectively and efficiently. By doing digital literacy, it is expected to be able to better understand and be able to have cognitive, communicative abilities, have the ability in creativity, have self-confidence and have a critical attitude in consuming media so as to avoid hoax and fake news, so that information received through social media can accountable for the truth. The conclusion of this study is the need to provide a set of literacy competencies, especially digital literacy when surfing the internet, including the importance of how to access the internet in a healthy and safe manner for students and a basic understanding of ethics and culture as well as searching for the right information on the internet, so that students can face challenges as global citizenship.